Aspirin Half Maximal Inhibitory Concentration Value on Platelet Cyclooxygenase1 in Severe Type-2 Diabetes Mellitus is not Significantly Different from that of Healthy Individuals. (September 2014) - Kimura, Yukio; Takano, Katsuhiro; Satoh, Kaneo; Aida, Kaoru; Kobayashi, Tetsuro; Ozaki, Yukio
It is implicated that diabetic patients are more resistant to aspirin therapy than patients with other diseases or healthy individuals. We evaluated the inhibitory effects of aspirin on aggregation and the cyclooxygenase activity of platelets of 10 patients with severe type-2 diabetes mellitis (DM) and compared the results with those of healthy individuals. Although platelet aggregation had a tendency to be more resistant to aspirin with the DM group, there was no significant difference in half maximal inhibitory concentration 50 values of aspirin on the cyclooxygenase activity between the patients with DM and healthy individuals. Thus, the residual platelet aggregability uninhibited by aspirin appears to be independent of the cyclooxygenase activity. Since adenosine diphosphate (ADP) receptor blocking almost completely inhibited the residual platelet aggregability, it is suggested that hyperreactivity to ADP is more prevalent in patients with DM.